The answer would be m^2+3m+2=0 because the first “part” of the equation (x^2-5) is equal to m; in the equation it’s squared so it can be replaced by m^2. next, 3m is the same as 3(x^2+5) which is what you have when you see 3x^2+15. finally, you have to bring the -2 over from the other side so you have positive 2. hope this helps!
We have that
<span>Bisector theorem--------------- >(LM)/(LN)=(OM)/(ON)
therefore
</span>(18)/(10)=(x)/(4)------------------ > x=7.2
the answer is x=7.2
Answer:
SSA (SIDE, ANGLE, SIDE)
Step-by-step explanation:
Answer:
g(x) = (x + 6)^2 - 5
Step-by-step explanation:
To translate f(x) to the left by 6 units, replace x with x+6.
To translate f(x) down 5 units, replace f(x) with f(x)-5.
Together, these replacements give you ...
... g(x) = f(x+6) -5
... g(x) = (x +6)^2 -5